Immunodetection of heparin-binding growth associated molecule (pleiotrophin) in striatal interneurons - Taravini, Irene Rita Eloisa (2005)
Pleiotrophin (PTN), a developmentally-regulated trophic factor, is over-expressed in the striatum of parkinsonian rats. Because striatal PTN can provide trophic support to dopamine neurons, we identified the cellular types containing PTN in the striatum of adult rats. By means of fluorescent double-immunolabeling, we found PTN to co-localize with a neuronal nuclei marker but not with glial fibrillary acidic protein. The number, distribution, and morphology of the PTN-immunolabeled cells suggested that they were interneurons. Further double-immunolabeling studies ruled out PTN localization to calretinin- and parvalbumin-containing interneurons. Instead, ∼40% of the PTN-immunolabeled neurons contained nitric oxide synthase or somatostatin and ∼60% expressed the vesicular acetylcholine transporter, supporting that they were GABAergic nitric oxide synthase/somatostatin-containing and cholinergic interneurons. Further work is necessary to determine if PTN from striatal interneurons can provide trophic support to dopamine neurons.